Evaluasi Implementasi Sistem Manajemen Kesehatan dan Keselamatan Kerja di Puskesmas Kabupaten Lombok Barat - Jamrah Jamrah; Saimi Saimi (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Risk control in healthcare facilities (fasyankes) creates a healthy, comfortable, safe, and secure working environment, so healthcare facilities need to implement an Occupational Health and Safety Management System (OHSMS/SMK3). Community health centers (Puskesmas) have not yet organized SMK3, so the implementation of SMK3 and the challenges faced need to be investigated. This study aims to understand the establishment of policies, planning, implementation, monitoring and evaluation, performance review and improvement, and the obstacles in implementing SMK3. This research uses an exploratory qualitative method aimed at understanding the implementation of SMK3 in Puskesmas in West Lombok Regency. Internal policy establishment and occupational safety planning are available and have been socialized, but there is no commitment from the leadership regarding occupational safety. Ten occupational safety standards in healthcare facilities have been implemented, except for regular health examinations or medical check-ups (MCU) which have not been carried out. The OHS team conducts routine monitoring every month and evaluates occupational safety every semester. There has never been any review or performance improvement activity conducted by external parties. The internal challenge is that many people still do not understand occupational health and safety (OHS) in health service facilities, so the implementation of OHS is not comprehensive, coupled with a lack of funding support. The external challenge identified is the absence of support from the relevant agency as the supervisor of OHS implementation at community health centers. The formulation of policies, planning, implementation, monitoring, and evaluation of OHS management systems has been carried out according to regulations but not in accordance with OHS policies, while the stage of review and performance improvement by external parties has not occurred, making the role of the health department as supervisor and overseer very necessary.Keywords: Implementation, OHS Management System, Community Health Centers, West Lombok.  ABSTRAK Pengendalian risiko di fasilitas pelayanan kesehatan (fasyankes) menciptakan lingkungan kerja sehat, nyaman, selamat, dan aman sehingga fasyankes perlu menerapkan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3). Puskesmas belum mengorganisasikan SMK3 sehingga  penerapan SMK3 dan kendala yang dihadapi perlu diteliti. Mengetahui penetapan kebijakan, perencanaan, pelaksanaan, pemantauan dan evaluasi, peninjauan dan peningkatan kinerja dan kendala dalam  penerapan SMK3. Penelitian ini menggunakan metode kualitatif eksploratif yang bertujuan mengetahui pelaksanaan SMK3 di Puskesmas Kabupaten Lombok Barat. Penetapan kebijakan internal dan perencanaan K3 tersedia dan sudah disosialisasikan namun belum ada komitmen dari pimpinan tentang K3. Sepuluh standar K3 di fasyankes sudah dilaksanakan hanya pemeriksaan kesehatan berkala atau MCU belum dilaksanakan. Tim K3 melaksanakan pemantauan  rutin setiap bulan, dan evaluasi K3 setiap semester. Belum pernah ada kegiatan peninjauan dan peningkatan kinerja oleh pihak eksternal. Kendala internalnya adalah masih banyak yang belum memahami K3 di fasyankes sehingga pelaksanaan K3 belum komprehensif dan kurangnya dukungan sumber dana. Kendala eksternal terdeteksi belum adanya dukungan dari dinas terkait selaku pembina pelaksanaan SMK3 di puskesmas. Penetapan kebijakan, perencanaan, pelaksanaan, pemantauan dan evaluasi SMK3 sudah dilaksanakan sesuai regulasi namaun belum sesuai dengan kebijakan K3, sedangkan tahap peninjauan dan peningkatan kinerja K3 pihak eksternal belum ada sehingga peran dinas kesehatan sebagai pembina dan pengawasan sangat diperlukan. Kata Kunci: Penerapan, SMK3, Puskesmas, Lombok Barat